Analyses of pathological cranial ultrasound findings in neonates that fall outside recent indication guidelines: results of a population-based birth cohort: survey of neonates in Pommerania (SNiP-study) - Judith Weise; Matthias Heckmann; Hagen Bahlmann; Till Ittermann; Heike Allenberg; Grzegorz Domanski; Anja Erika Lange (BMC, 2019)
Abstract Background Recent guidelines recommend a cranial ultrasound (CU) in neonates born at < 30 weeks gestation, admitted to the neonatal intensive care unit (NICU), or with a CU indication. Here, we addressed the need to extend these recommendations. Methods We retrospectively reviewed 5107 CUs acquired in the population-based Survey of Neonates in Pomerania, conducted in 2002 to 2008. Neonates with conspicuous CUs that were ≥ 30 weeks gestation without recent indications for CU were identified and assigned to the following groups: with (I) or without (II) admission to neonatal care. We designated CU conspicuities as mild (MC) or significant (SC), and we investigated related neurodevelopment during follow-up. Results Of 5107 neonates, 5064 were born at ≥30 weeks gestation and of those, 4306 received CUs without any indication for this examination. We found conspicuities in 7.7% (n = 47/610) of group I (n = 30 MC, n = 17 SC), and 3.2% (n = 117/3696) of group II (n = 100 MC, n = 17 SC). In group II, SC comprised, e.g., bilateral cysts, partial agenesis of the corpus callosum, and periventricular leukomalacia. Follow-up was available in 75% of infants in group II with MCs and SCs; of these, 12.8% had an abnormal neurological follow-up. Conclusions We detected a high number of conspicuities in neonates without a CU indication. However, we could not demonstrate that ultrasound findings were associated with the neurological follow-up or any advantage to an earlier diagnosis. Our data did not support extending current guidelines or a general CU screening policy for all neonates.